RB regulates the stability and the apoptotic function of p53 via MDM2. - Hsieh, J; Chan, F; O'Connor, D; Mittnacht, S; Zhong, S; Lu, X (1999)
The binding of RB to MDM2 is shown to be essential for RB to overcome both the antiapoptotic function of MDM2 and the MDM2-dependent degradation of p53. The RB-MDM2 interaction does not prevent MDM2 from inhibiting p53-dependent transcription, but the RB-MDM2 complex still binds to p53. Since RB specifically rescues the apoptotic function but not the transcriptional activity of p53 from negative regulation by MDM2, transactivation by wild-type p53 is not required for the apoptotic function of p53. However, an RB-MDM2-p53 trimeric complex is active in p53-mediated transrepression. These data link directly the function of two tumor suppressor proteins and demonstrate a novel role of RB in regulating the apoptotic function of p53.